2021
DOI: 10.1186/s43093-021-00073-w
|View full text |Cite
|
Sign up to set email alerts
|

The pillars determining financial inclusion among SMEs in Egypt: service awareness, access and usage metrics and macroeconomic policies

Abstract: Over the past decade, financial inclusion has been a trending topic and key priority in developing countries seeking to build a resilient financial sector and pursuing economic growth. Most of the recently launched financial inclusion initiatives in Egypt, especially those aligned with the 2030 sustainability strategy, have targeted marginalized and excluded individuals. Only a few have addressed the financial inclusion of small- and medium-sized enterprises (SMEs). Accordingly, this paper aims to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, the addition of new products, processes, and managerial activities involved in the delivery of a product or service can be understood to constitute innovation. Pedauga et al ( 2022 ) found a relationship between environmental sustainability practices and innovation and suggested that businesses should act following the ethics of corporate social responsibility (CSR) in their manufacturing practices by making use of new technology that is kind to the environment (Eldeeb et al 2021 ). This was based on Bansal’s finding a relationship between innovation and environmental sustainability practices.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, the addition of new products, processes, and managerial activities involved in the delivery of a product or service can be understood to constitute innovation. Pedauga et al ( 2022 ) found a relationship between environmental sustainability practices and innovation and suggested that businesses should act following the ethics of corporate social responsibility (CSR) in their manufacturing practices by making use of new technology that is kind to the environment (Eldeeb et al 2021 ). This was based on Bansal’s finding a relationship between innovation and environmental sustainability practices.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As a result, the incorporation of Islamic finance for business actors in the halal-tourist ecosystem is a must. Financial inclusion is defined as "the process of ensuring vulnerable groups, such as weaker parts and lowincome groups, access to financial services and timely and enough credit where needed at an affordable cost" [49]. The researcher can assess financial inclusion by examining access and impediments [10].…”
Section: Islamic Financial Inclusion and Business Performancementioning
confidence: 99%
“…According to Helmy's study (2021), human development and financial inclusion in Egypt have a negative association as a result of the widespread inequity in education and income, which may have negative effects on the level of economic development. ElDeeb et al, (2021) suggested three main pillars that determine financial inclusion in Egypt:…”
Section: -Literature Reviewmentioning
confidence: 99%